2010
DOI: 10.1089/ten.tec.2009.0604
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Topological Guidance for Cell Alignment via Direct Laser Writing on Biodegradable Polymer

Abstract: Direct laser writing on biodegradable polymer to create microchannels for aligning cells is presented here. This technique offers the advantages of ease-of-manufacturing, ease-of-design, high-speed single-step fabrication, and noncontacting to the material. In this work, microchannels of 100 microm width, 100 microm depth, and 50 microm intervals were created on a biodegradable polymer film directly using a Ti-sapphire femtosecond pulsed laser. Multiscale topological features were achieved as a result of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…Over the years, there are growing lines of evidence that insoluble cues or mechanical signals exert a significant influence in regulating stem cell differentiation. In line with this, several factors such as substrate stiffness, surface chemistry, and topography have been extensively studied to understand and predictably control stem cell differentiation, together with the concept of the stem cell niche [4][5][6]. Among these factors, the effects of matrix stiffness in directing a cell lineage have been extensively reported.…”
Section: Introductionmentioning
confidence: 97%
“…Over the years, there are growing lines of evidence that insoluble cues or mechanical signals exert a significant influence in regulating stem cell differentiation. In line with this, several factors such as substrate stiffness, surface chemistry, and topography have been extensively studied to understand and predictably control stem cell differentiation, together with the concept of the stem cell niche [4][5][6]. Among these factors, the effects of matrix stiffness in directing a cell lineage have been extensively reported.…”
Section: Introductionmentioning
confidence: 97%
“…[21][22][23][24] The alignment of CM has been studied for the last decade using different microfabrication (e.g., microcontact printing, abrasion, photolithography, hot embossing, electrospinning, and laser ablation) approaches. [25][26][27][28][29][30] Studies have also shown that these microtopographic cues have a greater effect on cell alignment than electrical cues. 25 However, while most previous studies examined the effects of mechanical cues at the 10s to 100s of microns, recent studies indicate that structure and function at the heart tissue level is exquisitely sensitive to mechanical cues at the nano-scale level as well.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber diameter of such 3D scaffold was measured to be a mixture of micro-(3.3 ± 0.6 µm) and nano-(240 ± 50 nm) fibers. The collected scaffold also replicates the inherent micro-nanoscale features in ECM that is essential in triggering series of cell activities [31][32][33][34][35][36] . The scaffold is therefore termed 3D multi-scale scaffold herein.…”
Section: Fabrication Of 3d Multi-scale Scaffold Using Hypodermic Needmentioning
confidence: 74%